Integrating silver compounds and nanoparticles into ceria nanocontainers for antimicrobial applications1. Issue 9 (7th March 2015) - Gagnon, J.; Clift, M. J. D.; Vanhecke, D.; Kuhn, D. A.; Weber, P.; Petri-Fink, A.; Rothen-Rutishauser, B.; Fromm, K. M.
<x xml:space="preserve">Abstract</x> Silver compounds and nanoparticles (NPs) are gaining increasing interest in medical applications, specifically in the treatment and prevention of biomaterial-related infections.